‘Social Cohesion’ and ‘Social Integration’ in Terms of Concepts and Models: A Türkiye-Germany Analysis (Third Sector Social Economic Review, 2025)
This study aims to provide a comparative analysis of the concepts of social cohesion and social integration in the context of forced migration, with a focus on the migration and integration policies of Türkiye and Germany. As a review article, it systematically examines academic literature, legal frameworks, and policy documents to assess how both countries address the challenges of integrating large immigrant populations. The choice of Türkiye and Germany stems from their contrasting governance models. Türkiye’s centralized and reactive policy orientation contrasts with Germany’s federal, long-term, and structured integration strategies, reflecting fundamental differences in migration management. The study argues that Türkiye prioritizes short-term cohesion under the temporary protection regime, whereas Germany emphasizes integration through structured programs based on federal cooperation. Furthermore, the article explores the impact of both countries’ social cohesion policies on social relations and institutions, while also discussing the role of migration policies in shaping broader social transformation. By comparing legal frameworks and practices, the study offers a nuanced perspective on how different governance contexts influence the effectiveness and direction of social integration and cohesion efforts.
Keywords: Forced migration; social cohesion; social integration; cohesion policies; integration programs